2007
DOI: 10.1080/01443610701469669
|View full text |Cite
|
Sign up to set email alerts
|

Obstetricians' attitudes towards ‘isolated’ oligohydramnios at term

Abstract: Oligohydramnios at term in the absence of maternal and fetal complications poses a dilemma in management. It is one of the major indications for antenatal surveillance and induction of labour. There is a growing body of evidence that oligohydramnios in the absence of maternal or fetal risk factors ('isolated' oligohydramnios) is not associated with an adverse perinatal outcome. In this study, we surveyed the management of isolated oligohydramnios at term in a tertiary referral maternity unit. Out of 92 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…Higher rate of isolated oligohydramnios (24%) was detected in a study in term 8 and this is double incidence as compared to other studies. [5][6][7] The AFV of 135 women was evaluated between 70 women (52%) in the upper greater group that was established by AFI and 65 women (48%) in the lower greater AFI group.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Higher rate of isolated oligohydramnios (24%) was detected in a study in term 8 and this is double incidence as compared to other studies. [5][6][7] The AFV of 135 women was evaluated between 70 women (52%) in the upper greater group that was established by AFI and 65 women (48%) in the lower greater AFI group.…”
supporting
confidence: 53%
“…IUGR, spontaneous rupture of membrane, diabetes, pre-eclampsia or severe maternal systemic diseases. 8 In a study by Chhabra, Dargan and Bawaskar; the overall labour induction during the study period of the retrospective cases was 18.2% but in oligohydramnios, it was 66.1%. The C/S rate in the retrospective cases with spontaneous labor was 42.4% and with induced labor it was 38.5%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fetuses in these cases tend to be appropriately sized at the diagnosis of isolated oligohydramnios and their perinatal outcomes are similar to those of pregnancies with a normal AFV 69 . The occurrence of such isolated oligohydramnios is more frequent at term 49,68,99 , which can be an additive factor toward a better outcome. .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the association between oligohydramnios and neonatal acidosis has not been sufficiently demonstrated; the observed adverse perinatal outcome results can be explained by the unnecessarily aggressive obstetrical management in the case of a reduced AF 59,62 . Other authors have found oligohydramnios to be a significant risk factor for an adverse perinatal outcome only in the presence of intrauterine growth retardation (IUGR) 66,67 , while isolated oligohydramnios in the third trimester does not seem to involve a risk of perinatal morbidity 68,69 .…”
Section: Analysis Of Oligohydramnios and Other Risk Factors In Cases mentioning
confidence: 99%